QUALITY MEASUREMENT CUSTOMER SATISFACTION INDEX (CSI) METHOD AND IMPORTANCE-PERFORMANCE ANALYSIS (IPA) DIAGRAM PT. ASDP INDONESIA FERRY (PERSERO) Merak – Banten - Gunawan, Akbar; Iqbal, Iqbal (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2018)
Service quality is a very important aspect to be considered to retain consumers. PT. ASDP INDONESIA FERRY (PERSERO) Merak Banten its duties as providers and services in the field of crossings. Measurement of customer satisfaction by using the method of the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA) diagram, Customer Satisfaction Index (CSI) value is 80,68%. which is the priority of improvement to improve customer satisfaction of PT ASDP INDONESIA that is in dimension of attributes intangible dimension is about toilet facility, this attribute need to be repaired because in its implementation there are still complaints from passengers and attributes that are contained in the dimensions responsiveness is regarding the speed and responsiveness in serving the passengers, responsiveness of the officer in providing information in providing the arrival and departure time , and the attributes contained in the assurance dimension is about the security level of the port area